Determining the potential of desmoglein 3 as a sensitive and specific immunohistochemical marker for the detection of micrometastasis in patients with primary oral squamous cell carcinoma - Nagvekar, Shruti; Spadigam, Anita; Dhupar, Anita (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Despite advances in surgical and radiotherapy techniques, the presence of lymph node metastasis drastically decreases the survival rate of patients with primary oral squamous cell carcinoma (OSCC). Thus the accurate pathological staging of the neck is critical. Desmoglein 3 (DSG3), a desmosomal cadherin protein is said to be highly expressed in head and neck squamous cell carcinoma (HNSCC) and in metastatic cervical lymph nodes, but absent in non-invaded nodes. With an aim to improve the sensitivity of tumour cell detection, we investigated the potential of DSG3 as an immunohistochemical marker for the detection of occult lymph node metastasis in patients with primary OSCC. Material and methods : Forty-seven lymph node specimens from 10 patients who underwent neck dissection for primary OSCC were immunostained with DSG3. Results : The DSG3 positivity was noted in the six positive lymph nodes. However, when using DSG3 as an immunohistochemical marker, no additional micrometastatic deposits were evident in the histologically negative nodes. Interestingly, tumour marker DSG3-positive macrophages could be identified within the subcapsular sinuses, medullary sinuses, and the interfollicular areas. Conclusions : Our findings suggest that although DSG3 is overexpressed in HNSCC, it is not specific and may not prove to be a potent immunohistochemical marker to detect micrometastasis. The role of tumour marker-positive macrophages within the lymph nodes needs to be investigated further.